A Critique of Banks’ Failure and Bankruptcy Law in Iran and the Necessity of Its Replacement with the Resolution System to Stabilize the Financial Sector in the Country - Mohammad Javad Sharifzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The issue of failure and bankruptcy of financial institutions, especially banks, is one of the most complex legal-economic issues that has generally been addressed within the framework of the usual rules of bankruptcy in private law. The experience of financial crises, especially the crisis of 2009-2008, showed that failure and bankruptcy of banks and other important financial institutions could lead to financial and economic instability. Consequently, in recent years, the issue of financial stability has become one of the main goals of economic and social policy makers, and the special system of bank failure (the so-called Resolution System) has become a pivot point of financial stability, so that many countries in the world have taken steps to create or develop a resolution system. This article, while introducing the resolution system, evaluates the legal system of Iran in terms of global standards in this field. The findings of the paper show that despite the fact that the legislators in Iran recognized the importance of the issue of bank failure and tried to partially divide the banks’ failure arrangements from the failure arrangements for other firms, the establishment of a resolution system for enhancing financial stability, and the strengthening of the economic system is urgent.